2013
DOI: 10.1167/iovs.12-11065
|View full text |Cite
|
Sign up to set email alerts
|

A Posteriori–Derived Dietary Patterns and Retinal Vessel Caliber in an Elderly Population

Abstract: This is the first study to investigate associations between a posteriori-derived DP and retinal vessel caliber. There was no evidence of a relationship between extracted DP and retinal vessel measurements in this population. However, it is possible that potentially important relationships exist between single nutrients or foods and vessel diameters that cannot be identified using a DP approach. Further studies to examine the role of dietary factors in the microcirculation are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Although some epidemiological investigations have shown a significant increase in the sale of ultraprocessed products, which between 2000 and 2013 increased by 43.7% worldwide [23,24], the traditional pattern was the most representative of our population. It includes food items similar to those studies conducted by Gutiérrez-Pliego et al [3] and Vilela et al [6], from Spain and Brazil, respectively, who named them as prudent, and McEvoy et al [25], who investigated diet patterns in several European countries and named them as healthy.…”
Section: Discussionmentioning
confidence: 95%
“…Although some epidemiological investigations have shown a significant increase in the sale of ultraprocessed products, which between 2000 and 2013 increased by 43.7% worldwide [23,24], the traditional pattern was the most representative of our population. It includes food items similar to those studies conducted by Gutiérrez-Pliego et al [3] and Vilela et al [6], from Spain and Brazil, respectively, who named them as prudent, and McEvoy et al [25], who investigated diet patterns in several European countries and named them as healthy.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, one trained researcher used a validated measurement and analysis protocol to objectively measure retinal vessel caliber as employed in previous studies [10][11][12][13][14]21]. Several potential limitations of this study should be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported inverse relationships between retinal vessel abnormalities and some dietary constituents such as dietary fibre [18], fish [19] and dairy intake [20]. However, adherence to a healthy or unhealthy derived dietary pattern was not found to be related to retinal vessel caliber measurement in European older adults [21]. To our knowledge, there are no published intervention studies examining the effect of dietary constituents on retinal vessel diameter.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations